VIDEOSURGERY TEACHING HISTORY - Rosa , Luciana Walger Collaço Gomes (2024)
Introduction: Surgical procedures were systematized and scientifically based at the end of the 19th century by William Stewart Halsted. Through scientific studies, anatomical principles, knowledge of physiology and pathology, strict aseptic techniques, gentle tissue manipulation, among others, were systematized. This lasted for centuries. But the modern technological era invented videosurgery and complicated the previously used teaching method. Objective: Review previously published teaching methods using simulators. Method: This is a narrative review carried out in the PubMed and Scielo databases. The search used the following keywords: videosurgery, teaching, simulators, training. The inclusion criteria comprised review articles and experimental studies, written in Portuguese and English and available in full text. The selected articles were analyzed based on the technologies covered, future perspectives and challenges mentioned. Result: 28 articles were included. Conclusion: As the results of this review on simulators show, once trained residents begin learning videolaparoscopic operations much more easily and safely.